2002
DOI: 10.1101/gad.969302
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of neural tube defects in Pax-3-deficient embryos by p53 loss of function: implications for Pax-3- dependent development and tumorigenesis

Abstract: Pax-3 is a transcription factor that is expressed in the neural tube, neural crest, and dermomyotome. We previously showed that apoptosis is associated with neural tube defects (NTDs) in Pax-3-deficient Splotch (Sp/Sp) embryos. Here we show that p53 deficiency, caused by germ-line mutation or by pifithrin-␣, an inhibitor of p53-dependent apoptosis, rescues not only apoptosis, but also NTDs, in Sp/Sp embryos. Pax-3 deficiency had no effect on p53 mRNA, but increased p53 protein levels. These results suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
174
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(181 citation statements)
references
References 33 publications
7
174
0
Order By: Relevance
“…This is consistent with the fact that Tead2 is expressed exclusively in mitotic neuroepithelial cells during fetal brain development (Jacquemin et al, 1996;Yasunami et al, 1995). Moreover, as previously reported for Pax3 mutants (Pani et al, 2002), injection of pregnant females with pifithrin-α, an inhibitor of p53 signaling (Murphy et al, 2004), suppressed exencephaly in Tead2 nullizygous females (Table 3B), suggesting that inhibition of apoptosis can rescue this NTD. However, the NTD seen in Tead2 nullizygous mice contrasts with that observed in Pax3 nullizygous mice.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is consistent with the fact that Tead2 is expressed exclusively in mitotic neuroepithelial cells during fetal brain development (Jacquemin et al, 1996;Yasunami et al, 1995). Moreover, as previously reported for Pax3 mutants (Pani et al, 2002), injection of pregnant females with pifithrin-α, an inhibitor of p53 signaling (Murphy et al, 2004), suppressed exencephaly in Tead2 nullizygous females (Table 3B), suggesting that inhibition of apoptosis can rescue this NTD. However, the NTD seen in Tead2 nullizygous mice contrasts with that observed in Pax3 nullizygous mice.…”
Section: Discussionsupporting
confidence: 90%
“…Pifithrin-α, an inhibitor of p53-dependent apoptosis (Murphy et al, 2004), has been reported to rescue NTDs in Pax3-deficient embryos (Pani et al, 2002). Similarly, pifithrin-α also prevented Tead2-dependent exencephaly to the same extent as did folic acid (Table 3B), suggesting that TEAD2 may regulate neural tube closure by inhibiting p53-dependent apoptosis, rather than by inducing neural tube-specific gene expression.…”
Section: Tead2 Is Involved In Neural Tube Closurementioning
confidence: 86%
See 1 more Smart Citation
“…We recently showed that Pax-3 down regulates p53 protein, and that NTD can be prevented in Pax-3-deficient Sp/Sp embryos by p53 deficiency [49]. Thus, apoptosis is ultimately responsible for the NTD associated with Pax-3 deficiency, but only because Pax-3 is needed to inhibit p53-dependent apoptosis until fusion of the neural tube is complete.…”
Section: Discussionmentioning
confidence: 99%
“…The paired-box domain is a highly conserved DNA-binding domain of 128 amino acids located at the amino terminus of the protein. Analysis of mouse models and human syndromes has revealed the importance of PAX genes in their role as regulators of normal development (Mansouri et al, 1999;Pani et al, 2002). Heterozygous splotch mice display pigmentary abnormalities while homozygotes die during gestation with spina bifida or exencephaly (Vogan et al, 1993;Auerbach, 1954).…”
Section: Introductionmentioning
confidence: 99%